THE INFLUENCE OF TASK-BASED LEARNING ON STUDENTS' READING COMPREHENSION AT SMA MUHAMMADIYAH BANGKINANG - Lidia Febrianti; Citra Ayu; Masrul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to investigate the effect of Task-Based Learning on students' reading comprehension in English language learning among tenth-grade students at SMA Muhammadiyah Bangkinang. The study employed a quasi-experimental design with a random sampling technique. The sample consisted of 60 students from two classes: X 2 as the experimental group and X 3 as the control group, with 30 students in each class. The students in the experimental group were taught using the Task-Based Learning approach, which emphasizes the use of meaningful tasks as the core of the learning process, while the students in the control group were taught using conventional teaching methods without the application of Task-Based Learning. Data analysis included validity and reliability testing, normality and homogeneity tests, and a t-test, which showed a significance value (2-tailed) < 0.05, specifically 0.178. Since the calculated significance value (0.179) is lower than the significance level (0.05), the researcher rejected the null hypothesis (Ho) and accepted the alternative hypothesis (Ha). This indicates that there is a significant difference in reading comprehension between students who were taught using the Task-Based Learning approach and those who learned through conventional methods. In conclusion, the findings suggest that implementing Task-Based Learning in reading instruction effectively improves students’ reading comprehension in English language learning. By engaging students in meaningful and goal-oriented tasks, this approach encourages active participation, promotes critical thinking, and enhances their ability to understand texts more deeply. As a result, students become more independent and confident readers who can interpret, analyze, and evaluate written information effectively